Modification of spasticity by transcutaneous spinal cord stimulation in individuals with incomplete spinal cord injury. (March 2014) - Hofstoetter, Ursula S.; McKay, William B.; Tansey, Keith E.; Mayr, Winfried; Kern, Helmut; Minassian, Karen
<x content-type="archive" xml:space="preserve">Abstract</x> Context/objective To examine the effects of transcutaneous spinal cord stimulation (tSCS) on lower-limb spasticity. Design Interventional pilot study to produce preliminary data. Setting Department of Physical Medicine and Rehabilitation, Wilhelminenspital, Vienna, Austria. Participants Three subjects with chronic motor-incomplete spinal cord injury (SCI) who could walk ≥10 m. Interventions Two interconnected stimulating skin electrodes (Ø 5 cm) were placed paraspinally at the T11/T12 vertebral levels, and two rectangular electrodes (8 × 13 cm) on the abdomen for the reference. Biphasic 2 ms-width pulses were delivered at 50 Hz for 30 minutes at intensities producing paraesthesias but no motor responses in the lower limbs. Outcome measures The Wartenberg pendulum test and neurological recordings of surface-electromyography (EMG) were used to assess effects on exaggerated reflex excitability. Non-functional co-activation during volitional movement was evaluated. The timed 10-m walk test provided measures of clinical function. Results The index of spasticity derived from the pendulum test changed from 0.8 ± 0.4 pre- to 0.9 ± 0.3 post-stimulation, with an improvement in the subject with the lowest pre-stimulation index. Exaggerated reflex responsiveness was decreased after tSCS across all subjects, with the most profound effect on passive lower-limb movement (pre- to post-tSCS EMG ratio: 0.2 ± 0.1), as was non-functional co-activation during voluntary movement. Gait speed values increased in two subjects by 39%. Conclusion These preliminary results suggest that tSCS, similar to epidurally delivered stimulation, may be used for spasticity control, without negatively impacting residual motor control in incomplete SCI. Further study in a larger population is warranted.